Conscientious Objection in Health Care: Why the Professional Duty Argument is Unconvincing. Issue 4 (3rd August 2022) - Symons, Xavier
Abstract: The past decade has seen a burgeoning of scholarly interest in conscientious objection in health care. Specifically, several commentators have discussed the implications that conscientious objection has for the delivery of timely, efficient, and nondiscriminatory medical care. In this paper, I discuss the main argument put forward by the most prominent critics of conscientious objection—what I call the Professional Duty Argument or PDA. According to proponents of PDA, doctors should place patients' well-being and rights at the center of their professional practice. Doctors should be prepared to set their personal moral or religious beliefs aside where these beliefs conflict with what is legal and considered good medical practice by relevant professional associations. Conscientious objection, on this account, should be heavily restricted, if even allowed at all. I discuss two powerful objections against PDA. The first objection, which I call the fallibility objection, notes that law and professional codes of conduct are fallible guides for ethical conduct and that conscientious objection has in the past and continues today to provide a check on aberrations in law and professional convention. The second, which I call the professional discretion objection, states that restrictions on conscientious objection undermine one of the cornerstones of good medical practice, namely, a practitioner's right to independent professional judgment. I argue that these two objections give us reason to retain conscience clauses in professional codes of conduct.